Trends in Antimicrobial Resistance of Acinetobacter baumannii and Pseudomonas aeruginosa from Bloodstream Infections: An Eight-Year Study in a Romanian Tertiary Hospital - Alina Maria Borcan; Elena Rotaru; Laura Georgiana Caravia; Mihai-Cezar Filipescu; Mădălina Simoiu (Pharmaceuticals)
Background: Bloodstream infections (BSIs) caused by multidrug-resistant non-fermenting Gram-negative bacilli, particularly Pseudomonas aeruginosa and Acinetobacter baumannii, represent a growing public health concern, especially in tertiary care settings. This study aimed to describe the epidemiological and antimicrobial resistance trends of P. aeruginosa and A. baumannii isolated from blood cultures over an eight-year period (2017–2024) at a tertiary infectious disease hospital in Bucharest, Romania, especially in the context of the disruption caused by the SARS-CoV-2 pandemic. Methods: A retrospective study was conducted on 43,951 blood cultures processed at the National Institute of Infectious Diseases. Species identification and antibiotic susceptibility testing (AST) were performed using VITEK2, MALDI-TOF MS, and supplementary phenotypic methods. AST interpretation followed EUCAST guidelines. Results: Out of all of the positive blood cultures, 112 (3.63%) were P. aeruginosa and 158 (5.12%) A. baumannii. Multidrug-resistance (MDR) was identified in 46% of P. aeruginosa and 90.73% of A. baumannii isolates. Resistance trends varied, with P. aeruginosa showing a decrease in MDR rates post-COVID-19 pandemic and following antimicrobial stewardship implementation. In contrast, A. baumannii displayed persistently high resistance, with carbapenem and aminoglycoside resistance rates reaching 100% by 2024. Colistin resistance, though low overall, increased in the latter years. Conclusions: The findings highlight the dynamic nature of antimicrobial resistance among P. aeruginosa and A. baumannii. Effective infection control and antimicrobial stewardship programs are crucial in curbing the rise of MDR strains, particularly amid healthcare system disruptions such as the COVID-19 pandemic.